"She Is NOT a Genuine Client": Exploring Health Practitioner's Mistrust of Rape Survivors in Nairobi, Kenya. (July 2018) - Munala, Leso; Welle, Emily; Hohenshell, Emily; Okunna, Nene
Sexual violence is one of the most common forms of violence against women in Kenya. Recognizing this, the Kenyan government introduced health care sector guidelines for survivors of sexual violence. This study explores the care of rape survivors from the perspective of health-care practitioners and identifies a number of recommendations for improving the quality of care. Qualitative interviews were conducted with 28 health practitioners from eight post-rape care facilities located in Nairobi, Kenya. Data were analyzed using the Colaizzi's 1978 analytical model. The study uncovered a troubling tendency of health practitioners questioning the authenticity of a woman's claim, deeming some not to be genuine rape survivors. Doubts about the veracity of the client's story led to additional emotional drain on health practitioners. This judgment negatively impacted the quality of care for rape survivors and in some cases, leading practitioners to deny services and exposing survivors to secondary victimization.